Implementasi Program Baca Tulis Al-Qur’an di Kabupaten Nganjuk Studi Multisitus SD Negeri Ngumpul I dan SD Negeri Ngumpul II Kecamatan Bagor - Mochamad Wahyudi; Isma Alfiana (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
In implementing the Al-Qur'an reading and writing program in Nganjuk district, the world of education is demanded to be able to make a real contribution, in the form of improving the quality of educational outcomes and services to the community. Innovation and creativity of educators as the spearhead are required to improve the quality of education in society. Islamic Religious Education subjects as a whole are divided into four scopes, namely Al-Qur'an and Hadith, Aqidah Akhlak, History of Islamic Culture, and Jurisprudence/worship. These four scopes at least illustrate that the scope of Islamic Religious Education is expected to be able to realize harmony and balance in human relations with Allah SWT, oneself, fellow humans, other creatures and their environment. This thesis is entitled Implementation of the Al-Qur'an Reading and Writing Program in Nganjuk district. A multi-case study at Ngumpul I Public elementary school and Ngumpul II Public elementary school Bagor Subdistrict with a research focus, namely 1. How is the planning of the Al-Qur'an reading and writing program at Ngumpul I Public elementary school and Ngumpul II Public elementary school II Bagor Subdistrict? 1. What is the Evaluation of the Al-Qur'an reading and writing program at Ngumpul I Public elementary school and Ngumpul II Public elementary school II? 2. How is the implementation of the Al-Qur'an reading and writing program at Ngumpul I Public elementary school and Ngumpul II Public elementary school, Bagor Subdistrict? 3. What is the evaluation of the Al-Qur'an reading and writing program at Ngumpul I Public elementary school and Ngumpul II Public elementary school, Bagor Subdistrict?